The Influence of Financial Reporting Quality on Information Asymetries in Company Management Strategies - Nugroho Budi Wirawan; Agustin Riyan Pratiwi; Hanny Gresya (Program Studi Pendidikan Ekonomi Universitas Pamulang, 2022)
The aims of this study is to evaluate the influence of value on information asymmetry, conservativeness, and timeliness of companies from 2013 to 2016, it was publicly listed and was involved in the industrial sector. A sample of this study used a sample of interest and a sample size of 312. The methods used to analyze the data were the regression analysis previously tested with the multicollinearity test, normality test, heterogeneity and test autocorrelation test. The results that the relevance of values does not affect the information asymmetry, as evidenced by the sig value. the count is greater than 0.05 ie 0.746 > 0.05. Then the conservatism variable does not affect information asymmetry. This is evidenced by the sig value. the count is greater than 0.05 ie 0.540 > 0.05. Then the timeliness variable does not affect the information asymmetry, this is proved by the sig value. count smaller than 0.05 ie 0.014 < 0.05.